Can Behenic Acid (C22:0) Levels be a Prognostic Factor in Glial Tumors? - Kaplan, Metin; Koparan, Mehmet; Sari, Aysel; Ozturk, Sait; Kaplan, Serpil Kozan; Erol, Fatih Serhat (Cambridge Univ Press, 2013)
Background: Inhibition of fatty acid synthase leads to apoptosis in cancers, which leads to high levels of fatty acid synthesis. This indicates that cancer cells depend on fatty acid in order to survive. In this study, we investigated whether or not there was a relationship between the glial tumor grade and free fatty acid level of tumor tissue. Methods: Twenty patients who had high grade glial tumors and 20 patients who had low grade glial tumors, were included in the study. Tumors samples were obtained intraoperatively in order to measure the fatty acid levels. The fatty acids were studied in three groups: saturated fatty acids, monounsaturated fatty acids and polyunsaturated fatty acids. They were analyzed with gas chromatography. Results: The oleic acid, linoleic acid, eicosadienoic acid, arachidonic acid, and docosadienoic acid levels were high in the tumor tissue of low grade tumors. The myristic acid, palmitic acid, stearic acid, alpha linoleic acid, eicosenoic acid, dihomo-gamma-linolenic acid, docosahexaenoic acid, and ceramide levels were high in the tumor tissue of high grade glial tumors. However, none of these high values were statistically significant. The high values of behenic acid, a saturated fatty acid, in low grade glial tumors were statistically significant. Conclusion: High levels of behenic acid in patients with low grade glial tumor is important as it indicates persistence of the tissue integrity and tissue resistance. behenic acid levels can be a prognostic factor in glial tumors.